Relationship Between Nutrition Knowledge and Dietary Patterns among Junior High School Students in Mataram City - Cahaya Safari; Kusmiyati Kusmiyati; Dewa Ayu Citra Rasmi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
In an effort to understand the factors influencing healthy eating habits among adolescents, there remains a lack of research that comprehensively examines the relationship between nutritional knowledge and dietary patterns of junior high school students in Mataram City. This study aims to determine the relationship between the level of nutritional knowledge and dietary patterns of students at public junior high schools in Mataram City. This study utilized a quantitative framework featuring a descriptive correlational method and a purposive sampling strategy to gather data from 317 seventh-grade pupils across 10 schools in Mataram City. The data were evaluated using the Pearson correlation method and the Chi-Square analysis. The findings revealed a positive and significant link between students' nutritional knowledge and their eating patterns, though the correlation was weak (r = 0.178; p = 0.002). These results suggest that enhancing nutritional knowledge may lead to improved dietary habits, but environmental and social influences are also significant. Further investigation is necessary to gain a deeper understanding of this relationship and to explore how other factors might affect the link between nutritional knowledge and student eating behaviors in a more thorough manner.